Visits in forests during the COVID-19 pandemic in the cross-border area of Poland, the Czech Republic and Germany - Ciesielski, Mariusz; Tkaczyk, Miłosz (Quaestiones Geographicae, 2023)
Mobile phone data were used to examine the differences in the number and structure of visitors to the Forest Promotion Complex Sudety Zachodnie in 2019 (pre-pandemic year) and 2020 (pandemic year). The studies not only compared the total number of visitors in each year, but also distinguished four pandemic and restriction periods. This allowed us to capture the dynamics of the impact of the pandemic on visits to forest areas. The results show that although the total number of visitors increased in 2020 compared to 2019, different trends were observed in each pandemic period. In general, the number of visitors to forest areas decreased during the first lockdown, as well as during the ban on entering green areas and forests. However, during the easing of restrictions and the second lockdown in the fall of 2020, there was an increase in visitor numbers. The article also shows the evolution of visitor numbers at a very detailed level of a grid of 750 × 750 m. During the pandemic, the structure of visitors also changed taking into account the place of residence. Local tourism was more important than national tourism. A significant decrease in the number of visitors from abroad was also observed, which is a consequence of the introduced restrictions on travel between countries. The methodology presented in this article can be used not only to study the impact of the pandemic on visits in forest, but also to manage forest areas with a view to adapting forest management to the needs of society.